Pembangunan modal insan sebuah negara bangsa: Pemerkasaan hubungan etnik dalam kalangan masyarakat Islam di Malaysia (Human Capital development in a nation state: Empowerment of ethnic relation among Muslim society in Malaysia) - Dahaman@Dahlan, Mohd Akram (2013)
Human capital development is an emphasized aspect by the world in developing a profitable and useful society to nation and their life.Malaysia also has taken continuous steps towards human capital development and has established it as a national main agenda. Malaysia is a Muslim majority country which consists of various ethnics and races such as Malay, Chinese, Indian and others. Moreover, Islam is the official religion of the country and it is stated in the highest constitution. On these facts, human capital development in Malaysia for the Muslim community from different races and ethnics should be based on the Islamic teachings according to al-Quran and as-Sunnah.Following the teachings of al-Quran, there are clear agendas in organizing Muslim society with various races and ethnics background.The agendas are to strengthen the multi-ethnics relationship in many aspects and are hoped to build a strong and united Muslim community.